A theoretical study of double-pass thulium-doped fiber amplifiers - Emami, Siamak Dawazdah; Harun, Sulaiman Wadi; Abd-Rahman, Faidz; Abdul-Rashid, Hairul Azhar; Daud, S.A.; Ghani, Zawajer Abd; Ahmad, Harith (Elsevier, 2010)
An efficient fluoride-based thulium-doped fiber amplifier (TDFA) is theoretically demonstrated using a double-pass scheme. A reflector is incorporated in the double-pass TDFA to allow double propagation of the test signal in the gain medium and thus improve the gain of the TDFA. The small signal gain improvement of more than 15 dB is obtained in the 1465 nm region. A gain as high as 42 dB is obtained in this region with 300 mW of 1050 nm pump using 20 m of thulium-doped fiber. However, a noise figure penalty of approximately 1 dB is also obtained in this wavelength region. Differential equations are solved using the Runge-Kutta method in the theoretical analysis. The theoretical result is in agreement with the experimental result.